Pengaruh Kepemimpinan Transformasional Terhadap Produktivitas Kerja pada Karyawan Badan Narkotika Nasional di Provinsi Sumatera Barat - Salsabilla, Ghina Syira; Ayu, Rindang (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This research is motivated by the importance of the role of leadership in improving employee work productivity in government agencies that have high demands for tasks and responsibilities. This study aims to determine the effect of transformational leadership on work productivity of employees at the National Narcotics Agency (BNN) in West Sumatra Province. The research method used is a quantitative method. The sampling technique uses a total sampling technique with a number of respondents totaling 176 BNN employees in West Sumatra Province. Data collection was conducted through a questionnaire with a Likert scale, and data analysis was performed using simple linear regression with the assistance of the IBM SPSS Statistics program. The results indicate that transformational leadership has a positive and significant effect on employee work productivity, with a regression coefficient of 0.930 and a significance level of <0.05. The coefficient of determination (R²) value of 0.787 indicates that 78.7% of employee work productivity is influenced by transformational leadership, while the remaining 21.3% is influenced by other factors not examined in this study. Based on these findings, it can be concluded that transformational leadership plays an important role in enhancing the work productivity of employees at the National Narcotics Agency in West Sumatra Province.